A community Milk Share initiative promoting health equity through Black community leadership - Mollard, Elizabeth; Gaines, Cydney; Boldt, Jillian; Hardesty, Jordan; Fynbu Eggert, Clara; Reddick, Ebony; Goodwin, Tina (Frontiers in Public Health, 2025)
Persistent racial disparities in breastfeeding reflect broader systemic inequities that disproportionately impact Black families. In response to barriers such as limited access to culturally competent lactation support, biased hospital practices, and financial constraints, Black-led, community-driven initiatives have emerged to improve breastfeeding success and infant nutrition equity. This community case study describes the development and implementation of the Malone Maternal Wellness Milk Share program, a Black-led initiative providing structured, community-based milk sharing to ensure equitable access to human milk. The program addresses systemic barriers by integrating rigorous donor screening protocols, informed consent processes, and culturally responsive lactation support while maintaining accessibility for families who might not otherwise have access to traditional milk banks. While created to address racial disparities, the Milk Share program is intentionally inclusive, welcoming all families in need regardless of race, ethnicity, or background. A Community Advisory Board guides the program, ensuring it remains aligned with both public health safety standards and the needs of Black families. By embedding donor human milk access within a broader framework of maternal health support, the Milk Share program demonstrates the effectiveness of community-led solutions in mitigating breastfeeding disparities and promoting infant health. The findings from this initiative underscore the need for healthcare systems and policymakers to recognize and support community-driven interventions as critical components of maternal and infant health equity efforts.